Liver Transplantation (LT) for Cryptogenic Cirrhosis (CC) and Nonalcoholic Steatohepatitis (NASH) Cirrhosis: Data from the Scientific Registry of Transplant Recipients (SRTR). Issue 31 (August 2018) - Golabi, Pegah; Bush, Haley; Stepanova, Maria; Locklear, Cameron T.; Jacobson, Ira M.; Mishra, Alita; Trimble, Gregory; Erario, Madeline; Venkatesan, Chapy; Younossi, Issah; Goodman, Zachary; Younossi, Zobair M.
Abstract : Abstract: Nonalcoholic steatohepatitis (NASH)-related cirrhosis and cryptogenic cirrhosis (CC) have become leading indications for liver transplantation (LT) in the US. Our aim was to compare the trends, clinical presentation, and outcomes for transplant candidates with NASH and CC. The Scientific Registry of Transplant Recipients (1994–2016) was used to select adult LT candidates and recipients with primary diagnoses of NASH and CC without hepatocellular carcinoma. Two lakh twenty-three thousand three hundred ninety-one LT candidates were listed between 1994 and 2016. Of these, 16, 214 (7.3%) were listed for CC and 11, 598 (5.2%) for NASH. Before 2004, NASH was seldom coded for an indication for LT, but became more common after 2009. Averaged across the study period, CC candidates compared with NASH candidates were younger and had fewer conditions of metabolic syndrome (MS). CC patients were more likely to have MS components in comparison to candidates with other chronic liver diseases (CLDs) (all P < .0001). For most of the study period, patients with CC or NASH were similarly more likely to be taken off the list due to deterioration or death, with to patients with other CLDs. Post-LT data were available for 14, 052 transplant recipients with NASH or CC. With the exception of post-transplant diabetes, the outcomes of patients transplanted for CC and NASH were similar to those of other CLD patients. Number of LT due to CC and NASH cirrhosis is increasing. In the past decade, there is a shift from LT listing diagnosis from CC to NASH potentially related to increased awareness about NASH in transplant centers in the US. Abstract : Supplemental Digital Content is available in the text